The Influence of Ambidextrous Leadership on Innovation Work Behavior at PT Petrokimia Gresik: The Mediating Role of Work Engagement and Moderating Role of Climate for Innovation - Achmad Afa Dzaudanilislam; Zuyyinna Noor Choirunnisa; Ansell Cohen Harjono (Manunggal Halim Jaya, 2026)
This research is motivated by the phenomenon of misalignment between the high administrative participation of employees in innovation activities and the contraction of financial performance at PT Petrokimia Gresik. The purpose of this study is to analyze the role of Ambidextrous Leadership in improving employee Innovation Work Behavior, specifically examining the mediating effect of Work Engagement and the moderating effect of Climate for Innovation. Methodology: This study uses a causal explanatory quantitative approach. A total of 464 organic employees were involved as respondents, selected through purposive sampling to ensure participants had relevant innovation experience. Data analysis was conducted using Structural Equation Modeling (SEM) with AMOS software and Bootstrapping estimation. Findings: The results show that Ambidextrous Leadership and Work Engagement have a positive and significant effect on Innovation Work Behavior. Work Engagement significantly mediates the influence of Ambidextrous Leadership on Innovation Work Behavior. Additionally, Climate for Innovation negatively moderates the relationship between Ambidextrous Leadership and Innovation Work Behavior, indicating a redundancy effect due to the organization's well-established innovation system. Theoretically, this study expands the understanding of innovative behavior antecedents through Dynamic Capabilities Theory. Practically, the results provide strategic input for management to formulate dual-focus leadership training and improve psychological well-being to accelerate impactful innovation.